Society of Flavor Chemists newsletter, July 1975 - Society of Flavor Chemists (1975)
July 1975 issue of the Society of Flavor Chemists newsletter.
Keywords: Society of Flavor Chemists; Newsletters; Flavoring essences; Flavoring essences industry; Flavor; Food additives; Food additives industry; Minutes (Records)